KEABSAHAN PEMBEBANAN HAK TANGGUNGAN TERHADAP HAK MILIK TANAH ADAT YANG MASIH DALAM PROSES KONVERSI KE HAK MILIK DI BADAN PERTANAHAN NASIONAL (BPN) DENPASAR - Angga Sumanjaya, Dewa Gede; Rudy, Dewa Gde; Sutama, Ida Bagus Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 09, September 2013)
Privately owning land which is used as a bond generally is a certified owningland, it could not be used as a bond if it is not certified yet unless conversion is doneand further load by hypothecation. How an uncertified land which still in conversionprocess could be loaded by hypothecation and how the process of hypothecationencumbrance to in conversion bond object. Empirical method is used in this research inDenpasar. It is done by searching and analyzing the facts concern to hypothecationencumbrance on in conversion bond object. Primary and secondary law materials areused. Those are analyzed using qualitative data processing by choosing data withappropriate quality to answers the problems and systematically present to obtain agood conclusion. Concerning to the legality of hypothecation encumbrance on bondobject which still in conversion, it is possessed by law. Such as customary rights landswhich are converted to land rights which stated by Article5 in 1960 of Agrarian AffairsPrincipal Base Rules, in administration process it is possible to be used as bond withhypothecation burden. The giving of hypothecation starts by making an agreement andcontinue by making hypothecation encumbrance power of attorney with notary officialdocument. After this process was finished the giving of hypothecation is done with landownership registration application in condition at the same time, it fulfill allregistration procedures.
Keywords: Privately Owning Land, Hypothecation, Bond, Conversion